The Influence Of Work’s Motivation And Compensation Effects Towards Employee’s Satisfaction, And The Impact On The Work Performance At State Employees Civil Sub Company, Kebun Jeruk, West Jakarta - Susan Novita Rotua Situmorang; Haryadi Sarjono (Universitas Airlangga, 2012)
Success in realizing the objectives company relies heavily on existing human resources in organizations in such company. To realize the objectives of the company, the company must consider factors that affect the performance of Civil Servants Work Motivation among others factors, Compensation, and Job Satisfaction. With the achievement of expected performance of Civil Servants Kebon Jeruk District Company can achieve its objectives. Kind research used is descriptive method, Pearson Correlation and Path Analysis is useful to know the response of employees on Work Motivation, Compensation for Job Satisfaction and Their Impacts on Civil Service Performance Kebon Jeruk District Company District Company where the employee population of 60 respondents. Provided the results of a calculation of the structural equation, Y = 0.579 X1 + 0.325 X2 + 0.644 ε1, where R2 = 0.585, sub-structure structural equation 2 ie, Z = 0.191 X1 + 0.239 X2 + 0.618 Y + 0.402 ε2 where R2 = 0.838 Conclusions and Recommendations of this research work motivation (X1) and Compensation (X2) jointly have a significant influence on job satisfaction (Y) equal to 58.8%. Work motivation (X1), Compensation (X2), and Job Satisfaction (Y) jointly have a significant influence on the performance of Civil Servants (Z) equal to 83.8%.